Somatostatin supports corneal wound healing in vivo - Hampel, Ulrike; Frömmling, Paul; Bräuer, Lars; Schaefer, Ivonne; Sel, Saadettin; Holland, Detlev; Paulsen, Friedrich (Annals of anatomy, 2016)
Purpose - To evaluate the influence of somatostatin (SST) and its analog octreotid (Oct) on corneal wound healing processes. - Methods - The wound healing rate in C57BL/6 mice eyes under SST and Oct treatment was analyzed using an alkali-induced corneal wounding model. Effects of SST and Oct on cell proliferation, migration and quantified protein expression of vascular endothelial growth factor (VEGF) on human corneal epithelial cells (HCE, cell line) were evaluated by means of electric cell-substrate impedance sensing, scratch migration assays and ELISA. ERK1/2 and p38 phosphorylation was investigated by semi-quantitative western blot analysis. - Results - Ten nanograms per microliters of SST significantly accelerated the wound closure rate of corneal defects in vivo. SST and Oct had no influence on HCE cell proliferation and migration and did not activate ERK1/2 or p38 signaling in HCE cells. However, there was increased VEGF protein expression in cytosolic proteins and medium supernatants of HCE upon Oct stimulation for 24h. One and 10ng/ml Oct led to a 2.5-fold and 100ng/ml Oct to a 4-fold upregulation of VEGF protein expression. - Conclusion - The data implicate that SST promotes corneal wound healing in a mouse model. However, using a HCE cell line in vitro, the wound healing mechanism does not seem to be supported by proliferation and migration processes or by activation of ERK1/2 and p38 signaling pathways. Other possible mechanisms could be the activation of other pathways and the induction of growth factors such as VEGF that modulate the observed corneal wound healing process.